Летучий самозванец: [роман] / Дарья Донцова - Донцова Дарья Аркадьевна (Иронический детектив, 2018)
Экземпляры: Ф. 3 (20190719) / Инвентарный номер: 46659 / Цена: 81.00 / Сис.шифр: Р2 / Авт.знак: Д 67 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-44